1978
DOI: 10.1159/000136811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydergine on Aging Neuroblastoma Cells in Culture

Abstract: Exposure of mouse neuroblastoma cells in culture to low pH for 8 days caused a sixfold increase in cell lipofuscin pigment. Pigment content was measured as the percent of cells having clumps of acid phosphatase-staining material. Hydergine, bétwen 0.1 and 3 μg/ml, caused a concentration-related decrease in pigment content. Hydergine also stimulated neurite formation in cells in regular pH medium and was slightly toxic to cells in low pH medium. These results support the use of neuroblastoma cells as an in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In the study of lipofuscin, the cell culture system has been regarded as a useful model. Cultured cells such as neurons [8][9][10], glial cells [11,12], neuroblastoma cells [13][14][15], cardiac myocytes [7,[16][17][18][19] and fibroblasts [20] are known to accumulate lipofuscin within a short period. In our laboratory, we have tested some cell lines to study the mechanism of lipofuscin formation in neurons and found that NG108-15 cells cease proliferation and accumulate lipofuscin-like autofluorescent materials during neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the study of lipofuscin, the cell culture system has been regarded as a useful model. Cultured cells such as neurons [8][9][10], glial cells [11,12], neuroblastoma cells [13][14][15], cardiac myocytes [7,[16][17][18][19] and fibroblasts [20] are known to accumulate lipofuscin within a short period. In our laboratory, we have tested some cell lines to study the mechanism of lipofuscin formation in neurons and found that NG108-15 cells cease proliferation and accumulate lipofuscin-like autofluorescent materials during neuronal differentiation.…”
Section: Introductionmentioning
confidence: 99%